Strategy Marketing E-Commerce in Era Technology 4.0 (Studies Case Platform Digital Ict Tok) - Diana Puspita sari; Muhammad Iqbal Fasa (Journal of Social Entrepreneurship and Creative Technology, 2024)
ABSTRACT Currently, the development of information technology is very complex and has many impacts on human life, including Internet business, namely E-Commerce which save time and does note require large capital to promote products. One of them is Tiktokshop which sell goods and services so that anyone can do business and compete at low costs. This website provides business opportunities and sell various products at more affordable prices than general stores To streamline its marketing, Tiktok shop is collaborating with Tokopedia. TikTok is known to be collaborating with PT GoTo Gojek Tokopedia Tbk (GOTO) with an investment of US$ 1.5 billion or around Rp. 23 trillion. Technology issuers GoTo and TikTok officially announced a strategic partnership on Monday 11 December 2023. This collaboration is here to strengthen the growth of Indonesia's digital economy with a focus on empowering and expanding the market for national MSME players. Therefore this research will analyze the Business to type E-Commerce marketing strategy Customers (B2C) use content analysis to provide an Overview of how to increase the effectiveness and efficiency of marketing strategies through E- commerce. In the era of the industrial revolution 4.0, the development of information technology is growing rapidly so that it can have an influence on society in support various business activities, both large and small, so that they can be known globally. With the development of information technology, sales volume and profits can be increased. Digital Marketing is a marketing medium that has a huge influence. This research is a qualitative descriptive research. Data was collected using the library research method. Using content analysis and deductive analysis, this research examine the marketing strategy of E-Commerce Tiktok shop. The research results show that Tiktok shop is an on line mall that provides on line business easily, while providing a safe and comfortable on line shopping experience for sellers and buyers because it has many of the latest features such US for sellers, creators, affiliates.